Lactic acid production from cane molasses by Lactobacillus delbrueckii NCIM 2025 in submerged condition: Optimization of medium component by Taguchi DOE methodology - Bhatt S.M.; Srivastava S.K. (My University, 2025)
Lactic acid production parameter optimization was performed using cane molasses by design of experiment (DOE) with the help of Qualitek-4 software with bigger is better as quality characteristics with eight media components at three levels in submerged culture condition. Eight factors with three levels studied were yeast extract, CaCO3, MnSO4, pH, Temperature, molasses, urea, and Tween 80. These factors were optimized based on their S/N ratios obtained from Qualitek-4 software and their significant individual interactions, and interactions with each other have been studied. Effects of mixed N2 sources, Tween 80, and MnSO4 have been studied by their individual interactions and interactions among themselves. Lactic acid production was significantly affected by interactions of two factors such as temperature-urea, pH-CaCO3, temperature-Tween 80, but individually they have minimum impact on lactic acid production. Individually pH, yeast extract, molasses, and urea are the most significant factors in lactic acid production. Lower amount of CaCO3 and MnSO4 and Tween 80 enhanced lactic acid production. The expected yield of lactic acid under optimal condition was 98.66% and the actual yield was 96.8%. Overall 6% improvement in yield has been observed when compared with same (mutant) species grown on cane molasses with productivity of 3.15 g/l.h. Copyright © Taylor & Francis Group, LLC.